Internet use and livelihood risk perception: exploring the dynamic relationship and moderating factors between information dissemination and individual perception - Gan, Xiaoli; Yang, Shuhan; Liu, Yaqian; Yu, Quan (Frontiers in Psychology, 2025)
IntroductionWhile the Internet brings development dividend to economy and society, it also changes the subjective attitude and risk perception of social members, which makes the complexity and uncertainty of economic society increasingly obvious. The development of economy and society is directly reflected in the livelihood issues, and consequently the widespread application of Internet has produced complex social effects on public perception of livelihood risks. This study explores the dynamic relationship and moderating factors between the Internet use and public perception of livelihood risks, considering various characteristics among different groups.MethodsThis study employs the data of China Family Panel Studies (CFPS) from 2014 to 2020, conducted on respondents aged between 16 and 65, which captures the majority of Internet users in China. Specifically, the analysis aims to examine the direct impact of Internet use on public livelihood risk perception, alongside the moderating influence of human capital and social capital. Moreover, the research discerns variations in the impact across different groups.ResultsOur findings reveal that Internet use significantly enhances the level of public livelihood risk perception, in which human capital and social capital exhibit a negative moderation effect. Furthermore, our findings highlight the heterogeneous effects of Internet use across diverse groups in livelihood risk perception. In addition, it is showed a steady decreasing tendency in the amplification effect of Internet on livelihood risk perception, while the COVID-19 made it temporarily rebound.DiscussionThis study explores the relationship between the Internet and public livelihood risk perception, as well as its dynamic changes, and to analyze how to effectively manage and mitigate the risks arising in the digital age. This extension not only enriches the theory system about the social amplification of risk, but also provides theory guidance for effective risk management. What’s more, this study reveals the weakening amplification effect of Internet on livelihood risk perception and fills the gap in most literature that only focuses on the negative result of the absolute amplification effect of Internet on social risks.